2022
DOI: 10.30865/mib.v6i3.4205
|View full text |Cite
|
Sign up to set email alerts
|

Penerapan Metode VIKOR (Visekriterijumsko Kompromisno Rangiranje) dalam Pengambilan Keputusan Pemilihan Emulator Android pada Komputer

Abstract: This research is a research on a decision support system in choosing the best android emulator to use on a computer as a topic of discussion. The Android emulator is a software that supports computers, both laptops and other computer devices, to be able to continue to access Android in computer use by simulating Android to a computer device. In choosing an android emulator, problems often arise to use which emulator is the best and in accordance with the specifications of the computer you have, so for this con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
1
0
1
Order By: Relevance
“…Metode penelitian dalam SPK merupakan serangkaian langkah yang digunakan dalam pengembangan, evaluasi, atau pemodelan sistem pendukung keputusan [14], [15]. Tujuannya adalah untuk memastikan bahwa SPK dapat memberikan dukungan yang optimal dalam pengambilan keputusan dengan mengoptimalkan kinerja, akurasi, dan nilai tambahnya [16], [17].…”
Section: Metode Penelitianunclassified
“…Metode penelitian dalam SPK merupakan serangkaian langkah yang digunakan dalam pengembangan, evaluasi, atau pemodelan sistem pendukung keputusan [14], [15]. Tujuannya adalah untuk memastikan bahwa SPK dapat memberikan dukungan yang optimal dalam pengambilan keputusan dengan mengoptimalkan kinerja, akurasi, dan nilai tambahnya [16], [17].…”
Section: Metode Penelitianunclassified
“…Research related to the selection of warehouse heads conducted by Satria (2023) the ranking results of the Visekriterijumsko Compromise Rangiranje (VIKOR) method in the selection of Warehouse Heads showed that the first rank with a final value of 0.045 was obtained by Candidate E [3]. Research conducted by Abdullah (2023) in recruiting warehouse heads by applying the MAUT method with ROC weighting with the best alternative decision results [4].…”
Section: Introductionmentioning
confidence: 99%